Hemorrhage promotes chronic adverse remodeling in acute myocardial infarction: a T1, T2 and BOLD study. (1st September 2020) - Assimopoulos, Stephania; Shie, Nancy; Ramanan, Venkat; Qi, Xiuling; Barry, Jennifer; Strauss, Bradley H.; Wright, Graham A.; Ghugre, Nilesh R.
Abstract : Hemorrhage is recognized as a new independent predictor of adverse outcomes following acute myocardial infarction. However, the mechanisms of its effects are less understood. The aim of our study was to probe the downstream impact of hemorrhage towards chronic remodeling, including inflammation, vasodilator function and matrix alterations in an experimental model of hemorrhage. Myocardial hemorrhage was induced in the porcine heart by intracoronary injection of collagenase. Animals ( N = 18) were subjected to coronary occlusion followed by reperfusion in three groups (six/group): 8 min ischemia with hemorrhage (+HEM), 45 min infarction with no hemorrhage (I − HEM) and 45 min infarction with hemorrhage (I + HEM). MRI was performed up to 4 weeks after intervention. Cardiac function, edema ( T 2, T 1 ), hemorrhage ( T 2 *), vasodilator function ( T 2 BOLD), infarction and microvascular obstruction (MVO) and partition coefficient (pre‐ and post‐contrast T 1 ) were computed. Hemorrhage was induced only in the +HEM and I + HEM groups on Day 1 (low T 2 * values). Infarct size was the greatest in the I + HEM group, while the +HEM group showed no observable infarct. MVO was seen only in the I + HEM group, with a 40% occurrence rate. Function was compromised and ventricular volume was enlarged only in the hemorrhage groups and not in the ischemia‐alone group. In the infarct zone, edema and matrix expansion were the greatest in the I + HEM group. In the remote myocardium, T 2 elevation and matrix expansion associated with a transient vasodilator dysfunction were observed in the hemorrhage groups but not in the ischemia‐alone group. Our study demonstrates that the introduction of myocardial hemorrhage at reperfusion results in greater myocardial damage, upregulated inflammation, chronic adverse remodeling and remote myocardial alterations beyond the effects of the initial ischemic insult. A systematic understanding of the consequences of hemorrhage will potentially aid in the identification of novel therapeutics for high‐risk patients progressing towards heart failure. Abstract : The individual and additive effects of hemorrhage in cardiac ischemia‐reperfusion injury are less understood. This work employs a unique preclinical model of myocardial hemorrhage and quantitative MRI relaxometry to probe the downstream consequences of hemorrhage. Our study demonstrates that the introduction of hemorrhage at reperfusion results in greater myocardial and microvascular damage, upregulated inflammation, chronic adverse remodeling, vasodilator dysfunction and extracellular matrix expansion in the distal remote myocardium, that are beyond the effects of the initial ischemic insult.